Non-verbal Enrichment in Vocabulary Learning With a Virtual Pedagogical Agent - Rosenthal-von der Pütten, Astrid M.; Bergmann, Kirsten (Frontiers in Psychology, 2020)
Non-verbal enrichment in the form of pictures or gesture can support word learning in first and foreign languages. The present study seeks to compare the effects of viewing pictures vs. imitating iconic gestures on learning second language (L2) vocabulary. In our study participants learned L2 words (nouns, verbs, and adjectives) together with a virtual, pedagogical agent. The to-be-learned items were either (i) enriched with pictures, or (ii) with gestures that had to be imitated, or (iii) without any non-verbal enrichment as control. Results showed that gesture imitation was particularly supportive for learning nouns, whereas pictures showed to be most beneficial for memorizing verbs. These findings, suggesting that the type of vocabulary learning strategy has to match with the type of linguistic material to be learned, have important educational implications for L2 classrooms and technology-enhanced tutoring systems.